Young Generation Emergency Awareness in The Tourism Area of Kemumu Village, North Bengkulu - Hasymi, Yusran; Utama, Tuti Angriani; Susilawati, Desi; Dianti, Feni Eka (Indonesian Journal of Community Services Cel, 2022)
Kemumu Village is a tourist destination that is visited by many people from various regions. The characteristics of the Kemumu Village tourist area has steep rocky areas, waterfalls, 1000-level stairs, cold temperatures, slippery roads, and has cross-country tourism activities. The problems that occur are frequent accidents due to falls that result in head injuries, spinal injuries, bleeding, drowning, fractures, shortness of breath, respiratory and cardiac arrest, and other emergency conditions. This condition poses a threat of disability and even death to the victim if it is not handled quickly and appropriately in tourist areas. Loss of life in tourists is bad news for the world of tourism. Therefore, it is necessary to carry out community service activities, especially the Young Generation regarding Emergency Alert (Gemu Gadar) in the tourist area of Kemumu Village, North Bengkulu. The activity method applied is lecture, discussion, and simulation for 10 people from Karang Taruna. Before giving the material, a pretest was carried out, followed by the provision of material on emergencies and simulations/practices. After that, posttest measurements were carried out. The results showed an increase in the knowledge and skills of participants in handling emergencies in the Kemumu tourist area.